Diagnostic and treatment model of post-intubation injuries of the trachea - Sadovyi , Valentyn; Kuchyn , Iurii; Bielka , Kateryna; Sazhyn , Dmytro (The Ukrainian Scientific Medical Youth Journal, 2023)
in medical practice, iatrogenic injuries caused by drugs or medical procedures are considered the most undesirable, as they are usually considered as intentional damage to the patient's health by the doctor. It is also impossible not to pay attention to the fact that such cases do not always have a favorable outcome. All this creates grounds for incorrect coverage of one's own record of failures and mistakes by specialists. The aim of the work was to study the available scientific data regarding iatrogenic post-intubation tracheal injuries and to form a diagnostic and treatment model of post-intubation tracheal injuries. Scientific articles, literature reviews and clinical cases of domestic and foreign authors related to iatrogenic injuries of the trachea are analyzed in the work. Most of the studied sources were not published later than 2018. Post-intubation tracheal ruptures are a rare but serious complication of intubation or tracheostomy. Mechanical and anatomical factors are among the risk factors of these complications. Most of them can be avoided by following the rules and recommendations when intubating patients. The main standards in the diagnosis of iatrogenic injuries of the trachea are X-ray and endoscopic evaluation, which allow detecting and characterizing suspected injuries. The use of the proposed medical-diagnostic model for assessing the severity of the condition of a patient with a tracheal injury can speed up diagnostic searches and help determine the therapeutic tactics of managing patient data. Treatment of post-intubation injuries can be conditionally divided into conservative, endoscopic and surgical. Separately, it is desirable to note the tactics of endoscopic stenting, which is becoming a viable alternative to surgical intervention, and not a backup option. The world's routine approach to the problem of post-intubation complications obviously only adds to the difficulties in the prevention and management of such patients. By themselves, such complications are not very frequent, but still remain extremely threatening and can lead to fatal consequences. And, unfortunately, insufficient discussion of such cases makes it difficult to develop algorithms for managing such patients. The proposed model of diagnosis and management of patients aims to improve the quality of treatment of such patients and reduce the number of possible complications.